Environmental Impact Assessment by Green Processes - Avino, Pasquale; Errico, Massimiliano; Giuliano, Aristide; Salehi, Hamid (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Primary energy consumption around the world has been increasing steadily since the Industrial Revolution and shows no signals of slowing down in the coming years. This trend is accompanied by the increasing pollutant concentration on the Earth's biosystems and the general concerns over the health and environmental impacts that will ensue. Air quality, water purity, atmospheric CO2 concentration, etc., are some examples of environmental parameters that are degrading due to human activities. These ecosystems can be safeguarded without renouncing industrial development, urban and economic development through the use of low environmental impact technologies instead of equivalent pollutant ones or through the use of technologies to mitigate the negative impact of high emissions technologies. Pollutant abatement systems, carbon capture technologies, biobased products, etc. need to be established in order to make environmental parameters more and more similar to the pre-industrialization values of the planet Earth. In 15 papers international scientists addressed such topics, especially combining a high academic standard coupled with a practical focus on green processes and a quantitative approach to environmental impacts.